Development of a pulse reconstruction routine for Transistor-Reset Preamplifiers for (n,xn) measurements using HPGe detectors at the n_TOF facility at CERN - Stamatopoulos, A.; Kokkoris, M.; Vlastou, R.; Patronis, N.; Tassan-Got, L.; Bosnar, D.; Tsinganis, A.; Diakaki, M.; Zugec, P.; Glodariu, T.; Negret, A.; nTOF collaboration, The (HNPS Advances in Nuclear Physics, 2019)
The knowledge of neutron induced cross-sections is essential both for applications as well as for the refinement of nuclear model parameters. Amongst other reactions, (n,xn) are equally important, however the determination of such cross-sections could be limited by current experimental techniques. In this respect, feasibility studies have been performed at the n_TOF facility at CERN concerning the study of (n,xn) reactions by detecting the prompt γ radiation emitted from the residual nuclei an experimental technique which required the use of a Transistor Reset Preamplifier (TRP) set-up. The digital acquisition system at n_TOF is accompanied by a pulse shape analysis framework which lacked the capability of dealing with TRP, therefore a new reconstruction routine had to be developed. A brief description and the first preliminary results are presented.